Discovery of Distinctin-Like-Peptide-PH (DLP-PH) From the Skin Secretion of Phyllomedusa hypochondrialis, a Prototype of a Novel Family of Antimicrobial Peptide - Wu, Di; Gao, Yitian; Tan, Yining; Liu, Yuzhang; Wang, Lei; Zhou, Mei; Xi, Xinping; Ma, Chengbang; Bininda-Emonds, Olaf R. P.; Chen, Tianbao; Shaw, Chris (Frontiers in Microbiology, 2018)
Amphibian skin secretions are an important treasure house of bioactive antimicrobial peptides (AMPs). Despite having been the focus of decades of research in this context, investigations of phyllomedusine frogs continue to identify new AMPs from their skin secretions. In this study, the prototype of a novel family of AMP distinctin-like-peptide-PH (DLP-PH) was identified from the skin secretion of the otherwise well-studied Tiger-Legged Tree Frog Phyllomedusa hypochondrialis through cloning of its precursor-encoding cDNA from a skin secretion-derived cDNA library by a 3'-rapid amplification of cDNA ends (RACE) strategy. Subsequently, the mature peptide was isolated and characterised using reverse-phase HPLC and MS/MS fragmentation sequencing. DLP-PH adopted an α-helical conformation in membrane mimetic solution and demonstrated unique structural features with two distinct domains that differed markedly in their physiochemical properties. Chemically synthesised replicates of DLP-PH showed antimicrobial activity against planktonic bacterial and yeast cells, but more potent against Escherichia coli at 32 µg/mL. However, DLP-PH showed much weaker inhibitory activity against the growth of sessile cells in biofilms. In addition, DLP-PH exhibited anti-proliferative activity against human cancer cell lines, H157 and PC3, but with no major toxicity against normal human cell, HMEC-1. These combined properties make DLP-PH deserving further study as an antimicrobial agent and further investigations of its structure-activity relationship could provide valuable new insights into drug lead candidates for antimicrobial and/or anti-cancer purposes.